2010
DOI: 10.1016/j.rbmo.2009.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Cycles triggered with GnRH agonist: exploring low-dose HCG for luteal support

Abstract: The aim of this study in patients at risk of ovarian hyperstimulation syndrome (OHSS) was to determine the efficacy and safety of luteal support using human chorionic gonadotrophin (HCG) after triggering ovulation with gonadotrophin-releasing hormone (GnRH) agonist in IVF/intracytoplasmic sperm injection antagonist cycles. A total of 192 OHSS-risk patients, following a GnRH antagonist protocol (0.25mg/day cetrorelix) during recombinant FSH stimulation, were triggered with 1.5mg s.c. leuproreline for ovulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 42 publications
0
33
0
2
Order By: Relevance
“…Adjuvant LH supplementation after a GnRH-agonist trigger has been administered in the form of a dual GnRH-agonist and lowdose hCG trigger (24), a low-dose hCG administered either 35 hours after a GnRH-agonist trigger (25,26) or intermittently during the luteal phase (27), and intermittent luteal phase recombinant LH administration (28). The main concern regarding the use of adjuvant low-dose hCG or recombinant LH is the potential recovery of CL function, which may increase the risk of OHSS development.…”
Section: Kummer Predictive Factors Of Gnrh-a Trigger Success Fertilmentioning
confidence: 99%
“…Adjuvant LH supplementation after a GnRH-agonist trigger has been administered in the form of a dual GnRH-agonist and lowdose hCG trigger (24), a low-dose hCG administered either 35 hours after a GnRH-agonist trigger (25,26) or intermittently during the luteal phase (27), and intermittent luteal phase recombinant LH administration (28). The main concern regarding the use of adjuvant low-dose hCG or recombinant LH is the potential recovery of CL function, which may increase the risk of OHSS development.…”
Section: Kummer Predictive Factors Of Gnrh-a Trigger Success Fertilmentioning
confidence: 99%
“…Although diff erent GnRH agonists have been used in GnRH antagonist cycles for the fi nal oocyte maturation in high-responders, no universal consensus has been defi ned regarding the optimal agonist kind and dose, and there is no report evaluating the impact of diff erent agonists on cycle outcomes. Among various GnRH agonists, buserelin 0.5 mg 14 , triptorelin 0.2 mg 15,16 and leuprolide acetate (0.5-4 mg) 17,18 have been utilized and almost all studies compared the outcomes of GnRH agonist triggered cycles with the cycles triggered with hCG. Most previous studies have reported successful oocyte maturation with 0.2-0.3 mg triptorelin, 0.5 mg buserelin and 1 mg leuprolide acetate [14][15][16]19 .…”
Section: Gnrh Agonistsmentioning
confidence: 99%
“…Ancak, %4,1 oranında orta ve %3,6 oranında ciddi OHSS komplikasyonları oluş-muştur. 22 Humaidan ve ark., yaptıkları birkaç ça-lışmada hem normo-responder hem de high-responder hastalarda yapılan GnRHa tetikleme sonrası HCG kullanımının reprodüktif sonuçları normalize ettiğini bildirmişlerdir. 16,17,23 Humaidan ve ark.…”
Section: 10unclassified